MECHANICAL VIBRATION ANALOGY OF A MANUFACTURING SYSTEM (Journal of Manufacturing Engineering, 2012)
Complexities of manufacturing system have been modeled by various modeling techniques viz. system dynamics modeling, discrete event simulation, mathematical models and various analogies. Manufacturing system continues to produce, in response to customer orders or stocking needs. This behavior is similar to mechanical vibration system which continues to vibrate in response to varying external force. Present work is an attempt to characterize manufacturing system in terms of mechanical system. Variation of displacement with time in mechanical system and variation of manufacturing in industry exhibits strong similarity. These plots must have similar root causes for matching behavior. This similarity between two plots forces modeling of one system into another. This concept is to visualize industrial system by way of equivalent mechanical system. The modeling is achieved by searching (m, c, k) values   of equivalent system. 3D search method is used to optimize the system properties. The model once developed can be manifested for enforcement of specific conditions of inputs or clarification of system properties for isolated effects.
Keywords: Manufacturing System; Mechanical Vibration; Dynamic Modeling